Pulmonary arterial pseudoaneurysm as an unusual complication of pulmonary actinomycosis: Two case reports - Aiko Urushibara, MD; Sodai Hoshiai, MD; Ken Koyama, MD; Moriyuki Kiyoshima, MD; Tatsuo Iijima, MD; Takahito Nakajima, MD (Radiology Case Reports, 2023)
We report 2 cases of pulmonary actinomycosis complicated by a pseudoaneurysm. In Case 1, a 67-year-old man visited a hospital 7 months ago because of hemoptysis. CT revealed a suspected lung abscess in the left lingular segment; however, no diagnosis was confirmed by bronchoscopy. A CT scan taken after heavy hemoptysis showed a pseudoaneurysm within the consolidation of the same segment. On the same day, embolization of the left bronchial and intercostal arteries was performed. Left lingulectomy was performed 5 days later, and pulmonary actinomycosis was diagnosed histologically. Case 2 was a 51-year-old man with a 2-year history of cough and intermittent hemoptysis. CT showed a lesion with a cavity suggesting an abscess 3 months previously, and antibiotic treatment was started. After the appearance of massive hemoptysis, embolization was performed for a pseudoaneurysm seen on bronchial arteriography. Four days later, a left lower lobectomy was performed, and pulmonary actinomycosis was histologically diagnosed. Pseudoaneurysms are commonly associated with tuberculosis; however, only one report of pseudoaneurysms has been associated with pulmonary actinomycosis. Appropriate treatment should be selected according to the type of pseudoaneurysm and the risk of recurrent hemoptysis. Angiography and embolization are essential tools in diagnosing and treating pulmonary arterial pseudoaneurysms; however, surgical intervention may also be an option in some cases to ensure a good long-term outcome.